Crypt cell proliferation and HLA-DR expression in pelvic ileal pouches. Issue 10 (October 1990) - de Silva, H J; Gatter, K C; Millard, P R; Kettlewell, M; Mortensen, N J; Jewell, D P
Abstract : To investigate the nature of the morphological changes that occur in ileal pouches, 26 biopsy specimens from patients with functioning ileo-anal pouches (eight with pouchitis) were studied. Normal ileum (n = 10) was used as a control. Mucosal morphometry (using linear measurements), crypt cell proliferation (CCP) (using the monoclonal antibody Ki67), and epithelial HLA-DR expression (monoclonal antibody CR3/43) were assessed. CCP (expressed as the percentage of Ki67 positive nuclei for each crypt) was significantly higher in pouches with pouchitis, compared with those without, and in pouches without pouchitis compared with normal ileum. CCP values in some pouches without pouchitis approached values found in those with pouchitis. CCP was related inversely to villous height and an index of villous atrophy (VH/TMT), and directly to crypt depth. In the presence of pouchitis there was intense epithelial HLA-DR expression that extended into the crypts. In some pouches with high CCP values, but without clinically important inflammation, surface epithelial HLA-DR expression was weak and patchy. It is concluded that villous atrophy and crypt hyperplasia in ileal pouches are associated with high CCP values. These may be increased even in the absence of active inflammation, and this increase may occur as a response to the new luminal environment.